Changes in tumour expression of programmed death-ligand 1 after neoadjuvant concurrent chemoradiotherapy in patients with squamous oesophageal cancer. (January 2016) - Lim, S.H.; Hong, M.; Ahn, S.; Choi, Y.-L.; Kim, K.-M.; Oh, D.; Ahn, Y.C.; Jung, S.-H.; Ahn, M.-J.; Park, K.; Zo, J.I.; Shim, Y.M.; et al.
Abstract: Background: Programmed death-ligand 1 (PD-L1) expression has been suggested as a potential predictive biomarker of response to anti-PD-1/PD-L1 therapy. In this study, we investigated whether the expression of PD-L1 in tumour cells is affected by neoadjuvant concurrent chemoradiotherapy (CCRT) or chemotherapy in oesophageal squamous cell carcinoma. Patients and methods: Between 2004 and 2014, we collected the medical records of locally advanced oesophageal cancer patients consecutively diagnosed and treated with neoadjuvant CCRT or chemotherapy, followed by curative resection. PD-L1 expression in acquired tissue specimens was evaluated by immunohistochemistry using the H-score. The changes in PD-L1 expression between paired samples were evaluated and we also analysed PD-L1 expression in surgical tumour specimens to evaluate its prognostic role. Results: Twenty-eight paired tumour tissues that were acquired before and after neoadjuvant therapy were available: 19 patients with CCRT and 9 with chemotherapy before complete oesophagectomy. The PD-L1 H-score increased significantly from baseline tumour tissues to surgical tumour tissues after neoadjuvant CCRT ( P = 0.007, median H-score from 28 to 52), whereas it decreased significantly after neoadjuvant chemotherapy ( P = 0.048, median H-score from 53 to 22). In a total of 73 patients, including 45 additional cases for the prognosis analysis, patients with higher PD-L1 H-scores (≥20) had poorer overall survival (median 16.7 versus 32.9 months, P = 0.02) than those with lower H-scores (<20). Conclusions: PD-L1 expression in tumour cells increased in oesophageal cancer patients who received neoadjuvant CCRT. Further studies with more cases are necessary to validate these findings. Highlights: We examined changes in programmed death-ligand 1 (PD-L1) expression in squamous oesophageal cancer tumour samples. PD-L1 expression in tumour cells significantly increased after neoadjuvant concurrent chemoradiotherapy. PD-L1 expression significantly decreased after neoadjuvant chemotherapy only. Radiotherapy could increase the tumour expression of PD-L1 within short time interval.